Mergers and acquisitions: Reason and results - Jyrki Ali-Yrkkö (The Research Institute of the Finnish Economy (ETLA), 2002)
The report looks at mergers and acquisitions (M&As) as companies' investment strategy. The aim of this study is to benchmark Finnish M&A activity against other countries. Several comparisons suggest that Finnish companies are very active in the M&A market. In fact, after taking into account the size of the economy, Finland ranked first out of all EU member states during the 1990s. This high level of activity is not only due to domestic deals but also to a high number of outward and inward crossborder mergers and acquisitions. Our analysis indicates that most of the cross-sectional and time-series variation of the M&A activity in different countries can be explained by using GDP, market capitalisation and the number of listed firms as explanatory variables. However, many other factors also explain the high Finnish M&A activity. Moreover, in this paper an eclectic model of the causes of M&As is also proposed. This schematic model suggests that there are macro-level, industry-level and firm-level factors affecting M&A decisions. – Merger ; acquisition ; takeover ; benchmarking ; M&A ; FDI – – Tässä raportissa tarkasteltiin yrityskauppoja yritysten investointistrategiana. Tutkimuksessa vertailtiin Suomen yrityskauppojen määrää muihin maihin. Useat vertailut osoittivat, että Suomessa tehdään poikkeuksellisen paljon yrityskauppoja. 1990-luvulla Suomessa tehtiin EU-maista eniten yrityskauppoja, kun huomioidaan talouden koko. Kotimaisten yrityskauppojen lisäksi suomalaiset yritykset ovat olleet mukana myös kansainvälisissä yritysjärjestelyissä. Maiden välistä eroa yrityskauppojen lukumäärässä voidaan selittää BKT:lla, pörssin markkina-arvolla sekä listattujen yritysten lukumäärällä. Nämä tekijät eivät kuitenkaan yksi riitä selittämään Suomen korkeaa yrityskauppa-aktiviteettia. Tässä raportissa esitellään lisäksi kehikko, jonka mukaan yrityskauppapäätösten takana on sekä makrotaloudellisia, toimialakohtaisia että yrityskohtaisia tekijöitä. – Yrityskauppa ; fuusio ; vertailu ; M&A ; ulkomainen investointi
Keywords: 330; Fusion; Übernahme; Benchmarking; Direktinvestition